MINAT JURNALIS KOMPAS TV MELIPUT BERITA INVESTIGASI - Siti Sarifah (Program Studi Ilmu Komunikasi, 2021)
Interest is the encouragement or desire of someone pleasant, can provide satisfaction, and becomeenergy to increase morale when carrying out work. So far, reporting investigative news is still considered to be ahigh-cost, time-consuming report because it requires a long time, high difficulty, and great risk. This, of course,causes low interest in becoming investigative news journalists, because it requires strong capital requirements,tenacity, and patience that journalists must have in carrying out investigative news coverage. This research wasconducted using a qualitative approach by conducting in-depth interviews, participating in daily operationalactivities of the data sources, and based on existing documentation. The purpose of this study is to find out howinterested Kompas TV journalists are in covering Investigation News. Based on the research results, it wasfound that the interest of Kompas TV journalists in covering investigative news in the program "File Kompas"with high enthusiasm resulted in many awards that have been obtained. Cognitive personal interest in coveringinvestigative news was owned when they were in college, then strengthened during an internship. Then, theaffective element is obtained from daily interactions as well as activities in the journalist community of KompasTVKeywords: Interests, Cognitive, Affective, Investigation News.